2022
DOI: 10.1186/s40364-022-00393-1
|View full text |Cite
|
Sign up to set email alerts
|

circCYP24A1 promotes Docetaxel resistance in prostate Cancer by Upregulating ALDH1A3

Abstract: Background Docetaxel (DTX) is the most widely prescribed first-line chemotherapy for advanced prostate cancer (PCa). Unfortunately, DTX resistance invariably emerges, leading to worse prognosis of PCa. Growing evidence has shown that circRNAs had complex spatiotemporal specificity during the tumor development and oncogenesis. This study was designed to investigate the biological functions and possible molecular mechanisms of circRNAs in DTX resistance of PCa. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 50 publications
2
4
0
Order By: Relevance
“… 35 Furthermore, abnormal expression of ALDH1A3 promotes chemotherapy resistance in prostate cancer, via the PI3K/AKT/mTOR axis. 36 Our study revealed a potential regulatory mechanism between ALDH1A3 and the PI3K/AKT/mTOR axis, which is consistent with previous studies. Reports have shown that malignant tumor cells utilize aerobic glycolysis to accumulate pyruvate, lactate, and glutathione, thus enhancing their antioxidant activity and resistance to the harmful effects of free radicals and oxidative stress resulting from radiotherapy.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“… 35 Furthermore, abnormal expression of ALDH1A3 promotes chemotherapy resistance in prostate cancer, via the PI3K/AKT/mTOR axis. 36 Our study revealed a potential regulatory mechanism between ALDH1A3 and the PI3K/AKT/mTOR axis, which is consistent with previous studies. Reports have shown that malignant tumor cells utilize aerobic glycolysis to accumulate pyruvate, lactate, and glutathione, thus enhancing their antioxidant activity and resistance to the harmful effects of free radicals and oxidative stress resulting from radiotherapy.…”
Section: Discussionsupporting
confidence: 93%
“…It has been reported that ALDH1A3 activates the PI3K/AKT/mTOR signaling pathway by cross‐talking with the transcription factor PPARγ in pancreatic cancer 35 . Furthermore, abnormal expression of ALDH1A3 promotes chemotherapy resistance in prostate cancer, via the PI3K/AKT/mTOR axis 36 . Our study revealed a potential regulatory mechanism between ALDH1A3 and the PI3K/AKT/mTOR axis, which is consistent with previous studies.…”
Section: Discussionsupporting
confidence: 92%
“…It is showed that circRNAs participated in tumor progression by activating multiple signal pathways such as β-catenin signaling [ 6 ], AMPK-mTOR pathway [ 8 ], TGF-β pathway [ 18 ], PI3K/AKT/mTOR signaling pathway [ 29 ]. To investigate the downstream signaling pathways involved in circCYP24A1, we performed mRNA expression profile microarray and found that circCYP24A1 was involved in regulation of cell proliferation and TNF signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…To make clear the functional mechanism, the subcellular localization of circCYP24A1 in ESCC cells was detected and FISH revealed that most of circCYP24A1 localized in cytoplasm. CircRNAs located in the cytoplasm could acts as ceRNAs competitively bind miRNAs [ 18 , 29 , 30 ] and bind to RBPs [ 6 , 8 , 18 , 19 ]. A few cytoplasmic circRNAs also have the ability of translating novel polypeptides or proteins [ 16 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation